Taiwan Neurosurgical Spine Society: The New Shining Star - Kuo, Yi-Hsuan (Neurospine, 2018)
As spine surgery flourished in Taiwan and neurosurgeons became more involved in spine surgery towards the end of the 20th century, the Taiwan Neurosurgical Spine Society (TNSS), earlier named the Taiwan Neurospinal Society, was established on March 11, 2001. As its main founder, Dr. Chun-I Huang was elected as the first president of the TNSS. The goals of the TNSS were to promote research, to hold academic seminars, to participate in international conferences, and to exchange clinical experiences. The mission of the TNSS was successful, and the profession of spine surgery in Taiwan advanced during the first decade of the 21st century, culminating in the TNSS joining ASIA SPINE in 2010. Since its establishment, the TNSS has always been supportive of collaboration and communication with the Korean Spinal Neurosurgery Society and the Neurospinal Society of Japan. Through periodical meetings, supported by the TNSS, surgeons worldwide have enjoyed a platform of sharing and mutual learning. To further promote academic research, the TNSS has officially supported the journal Neurospine since 2018. With extensive efforts from local and international surgeons, the TNSS will continue to adhere to its mission and to advance the profession of spine surgery.